A comparison between rural and urban pre-retiree government agensy employees in Iloilo preparedness, perception and coping strategies on retirement. - Napuli, La Donna M. (2010.)
A total of 40 (28) female and (12) male respondents aged 45-50 years old participated in the study. A 5 point 40 item Likert-like questionnaire ( Serios & Sta., Rufina, 2001) was utilized to determine the views on retirement. Respondents who scored 40-119 exhibits negative view on retirement while those who scored 120-200 has a positive view towards it. Another survey questionnaire developd by Domingo and Naldoza (2005) was employed by the reearchers to determine the level of preparedness of pre-retiree government employees. The Revised Ways of Coping Checklist (Lazarus & Folkmann) was also employed to find out the coping strategies that respondents commonly use., Resutls showed that most respondents have positive views towards retiremnet but they are not financially and emotionally prepared. They tend to use seeking socail support, problem-focused, religiosity, wishful thinking as coping strategies. Furthermore, it was found out that there is no significant difference between the views, level of preparedness, and coping strategies among rural and urban pre-retiree government employees.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo.
Keywords: Retirees -- Rural -- Iloilo; Retirees -- Urban -- Iloilo; Pre-retiree Government Agency Employees -- Iloilo